Assessment of musculoskeletal symptoms in academics in full‑time and part-time courses - Antonelli, Gabriela; Gomes, Jossinelma Camargo; Oliveira, Marcio Antonio Klingelfus de; Baroni, Marina Pegoraro (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Musculoskeletal symptoms are affections, with or without degeneration of the tissues, and may present in various forms and be associated with multiple symptoms. At the moment its etiology is multifactorial and the pathological picture shows social relevance due to its scope and magnitude. Objective: The objective of this study was to evaluate and compare the prevalence of musculoskeletal symptoms in academics of full-time and part-time (nighttime) courses at UNICENTRO. Methods: The study counted on 120 students of both courses and for the selection of the individuals was used the stratified sampling method. The Nordic questionnaire for musculoskeletal symptoms (NMQ) and Visual Analogue Scale (VAS) questionnaire were used as a form of pain identification. Results: Observing the results obtained from the NMQ, it was observed a high prevalence of symptoms in the analyzed students, being 49% in Biological Sciences and 44.8% in Physiotherapy, highlighting the region of the vertebral column, being lumbar (9.42%) in academics of Physiotherapy and thoracic region (9.14%) in academics of Biological Sciences, also noted high involvement in multiple regions (53.9%). Furthermore, it was observed the presence of mild pain trough VAS (3.78 ± 2.38). Conclusion: It was concluded that the most affected region was the spine, specifically the lumbar and thoracic. Thus, it is assumed that biomechanical overload is responsible for this finding. Thus, preventive and ergonomic measures and health promotion should be stimulated among young students, but for this purpose further studies are needed.